Profile of Hydrogen Peroxide (H2O2) Levels in Hyperglycaemic Wistar Rats (Rattus novergicus) After Olive Oil (Olea europaea) Administration - Yorencia Akmal; Husnil Kadri; Almurdi Almurdi; Ety Yerizel; Roza Mulyana; Erlina Rustam (Universitas Pahlawan Tuanku Tambusai, 2026)
Objective: Objective: To examine the effect of olive oil on hydrogen peroxide ROS levels that cause diabetes mellitus/hyperglycaemia in Wistar rats after being induced with the diabetogenic substance alloxan over a period of 14 days. Hydrogen peroxide (H2O2) is one indicator of ROS (Reactive Oxygen Species) to determine the state of cell oxidative stress. The increase in ROS in the body is caused by an imbalance between ROS and anti-oxidant enzymes, so that triggers biological cell damage, including oxidation of carbohydrates, proteins, fats, DNA. Oxidation of β-pancreas cells causes a decrease in the sensitivity of cell tissue to insulin, so that blood glucose concentrations increase. Blood sugar levels ≥ 200 mg/dL indicate chronic diabetes mellitus or hyperglycaemia. Olive oil contains secondary metabolite compounds such as phenolic and can neutralise H2O2 in blood serum. Methods: This study used 24 male Wistar rats, and grouped into three groups, namely negative control (K-), positive control (K+) and treatment (P) with observation for 14 days. Results: from the results of statistical analysis based on the Mann Whitney test and Kruskal Wallis test, the average difference was obtained at p ≤ 0.05. From the data analysis showed the effect of olive oil antioxidants in reducing H2O2 levels gave significantly different effects on each group, respectively, K (-) 4.838 mmol/mL, K (+) 20.888 mmol/mL and P 18.193 mmol/mL. Conclusion: Olive oil administration has an effect on reducing hydrogen peroxide (H2O2) levels in hyperglycaemic Wistar rats.